Congenital optic disc cyst concomitant with persistent hyaloid artery – a case report - Modrzejewska, Monika; Lachowicz, Ewelina; Tokarz-Sawińska, Ewa; Lubiński, Wojciech; Koryzma, Adam; Walecka, Anna; Urasiński, Tomasz; Zajączek, Stanisław (Klinika Oczna / Acta Ophthalmologica Polonica, 2013)
The aim is to present a rare case of solitary malformation in the form of a congenital optic disc cyst concomitant with the persistent hyaloid artery. The intrabulbar congenital cyst of the optic disc partially covering the medial part of the disc was found in a 3-month old infant. B-San ultrasound confirmed the presence of the intrabulbar heterogeneous mass (7.0 x 2.5 x 5.4 mm) within the vitreous cavity and the concomitant persistent hyaloid artery was shown in Colour Doppler Imaging. The axial length of the involved eye was shorter than of the healthy one (16.68 mm vs. 18.42 mm). The magnetic resonance imaging of the head and orbits performed in the fast spin echo, spin echo and gradient echo sequences in T1 and T2-weighted scans revealed the intrabulbar cyst (7.0 x 2.5 x 6.4 mm), with sharp margins, whose lower part showed intense contrast enhancement. The pericerebral fluid spaces within the frontal and temporal lobes were dilated. Intrauterine toxoplasmosis, cytomegaly, protozoan and helminth infections as well as metabolic diseases were excluded. Patient leukocyte DNA RB1 gene sequencing and negative results of mutation searching excluded retinoblastoma. In a 2-year follow-up period, regression of the mass with the absence of ophthalmic complications was noted. An important reason for the authors to present the discussed case is possible permanent impairment of visual function in patients with similar presentation of congenital peripapillary lesions.